2012
DOI: 10.1002/ppul.22608
|View full text |Cite
|
Sign up to set email alerts
|

A 4 year prospective study to determine risk factors for severe community acquired pneumonia in children in southern China

Abstract: Young age and underlying congenital heart disease were associated factors for PICU support in CAP in China. Early referral if altered sensorium, high respiratory rate, head nodding, grunting and anemia, and universal access to conjugated vaccines may decrease morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
59
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 28 publications
8
59
2
2
Order By: Relevance
“…They found that young age (≤12 months old) and congenital heart diseases were significantly associated with the need for intensive care admission. They also found that children with Down syndrome and immunodeficiency had higher mortality [18]. Unlike Zhang et al’s study, in our cohort, a diagnosis of chronic lung disease not congenital heart disease was associated with life- threatening LRTIs.…”
Section: Discussioncontrasting
confidence: 67%
“…They found that young age (≤12 months old) and congenital heart diseases were significantly associated with the need for intensive care admission. They also found that children with Down syndrome and immunodeficiency had higher mortality [18]. Unlike Zhang et al’s study, in our cohort, a diagnosis of chronic lung disease not congenital heart disease was associated with life- threatening LRTIs.…”
Section: Discussioncontrasting
confidence: 67%
“…Association of underlying congenital heart disease with pneumonia mortality reported between 7-12% within the groups [5] is comparable to other studies from India though much higher figures have been reported from China [2]. Presence of co-morbidities, in this study particularly diarrhea and HIV, has been reported as an important risk factor for severe pneumonia in areas with high prevalence of HIV [4].…”
supporting
confidence: 83%
“…A study from Delhi [1] has demonstrated this important association of severity of illness with CFR ranging from 0-47% in children with pneumonia, severe pneumonia, and very severe pneumonia as per WHO classification. In the study by Ramachandran, et al [5] 47-68% of the children who died required assisted ventilation which is much higher than reported by others [2]. It is difficult to understand the VOLUME 49 __ NOVEMBER 16, 2012 EDITORIALS practical importance of this association because the clinical course and pathway to death can not be visualized if the cases are not categorized based on severity of illness at the time of admission.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…In previous literature, iron deficiency has been reported as a comorbidity associated with influenza A . In addition, anaemia has been identified as a risk factor for respiratory failure in children admitted to hospital for community‐acquired pneumonia . Iron has many important functions in the body including regulation of the immune system, and therefore, deficiency could compromise immune function and impact on acquisition and severity of infections including influenza.…”
Section: Discussionmentioning
confidence: 99%